Toward Efficient Oil Energy Recovery Eco-Friendly Fabrication of a Biomimetic Durable Metal Mesh with a Moss-Like Silver Nanocluster Structure - Zhu, Meng (Langmuir : the ACS journal of surfaces and colloids, 2021)
With the purpose of oil energy recovery as well as achieving efficiency of oil/water separation, hydrophobic mesh materials have attracted extensive attention. However, fabrication of the current methods is not environmentally friendly, has high energy consumption, and creates serious pollution. Inspired by lotus leaves and rose petals, a biomimetic superhydrophobic surface was fabricated prepared on a stainless steel mesh by an in situ chemical reduction method with simple operation and mild conditions. The results of SEM, XRD, and XPS demonstrated that the mesh shows a stable and uniform moss-like rough structured surface. The SSM/Ag/ODA mesh, which was modified by moss-like Ag nanoclusters and low surface energy agents, has excellent superhydrophobicity with an excellent oil/water separation efficiency that reached up to 99.8%. The silver mirror phenomenon formed by the Ag nanoclusters further confirmed that silver ions were reduced and attached to the surface of the mesh. Moreover, the mesh can maintain superhydrophobicity under harsh conditions, such as a high concentration of a salty solution, organic solvents, alkaline, acidic solution, and even long-time UV irradiation, etc. More importantly, the modified mesh has excellent physical stability, in which the water contact angle on the mesh can be maintained above 150° after harsh mechanical wear. The hydrophobic mesh showed great potential to be applied for highly efficient oil/water separation and oil energy recovery even under complex and harsh conditions